Pengaruh Konektivitas Infrastruktur terhadap Pertumbuhan Ekonomi dan Pariwisata Lampung: Perspektif Ekonomi Islam 2015-2024 - Diah Ayu Permata; Madnasir Madnasir; Nur Wahyu Ningsih (Perbanas Journal of Islamic Economics and Business, 2026)
This study examines in depth how infrastructure connectivity influences the dynamics of economic growth and the performance of the tourism sector in Lampung Province for the period 2015–2024, using an Islamic economic perspective as the main analytical basis. The data used are sourced from official statistics from BPS, the PUPR Office, and the Lampung Tourism Office, which are then processed through a quantitative approach using the Vector Autoregression (VAR) model, including the stages of optimal lag testing, model stability, cointegration, Granger causality, and stationarity testing at the second difference level. The estimation results show that the VAR model is stable with an optimal lag of 2 and does not find a long-term cointegration relationship or significant causality between the variables of Economic Growth, Tourism Sector, and Infrastructure Connectivity. The coefficient of determination value of 87.4% indicates that infrastructure connectivity is able to explain most of the movements in economic growth and the tourism sector, although the partial effect of infrastructure connectivity on economic growth is positive but not significant (coefficient of 3.016), while its effect on the tourism sector is negative and remains insignificant (coefficient of -52.079). From an Islamic economic perspective, these findings emphasize the importance of integrating physical infrastructure development with strengthening human resource quality and governance based on maqashid al-shariah, including social justice, public welfare, and environmental preservation to respond to the risks of overtourism and unequal distribution of benefits. Thus, unlike conventional studies, this research offers a normative-empirical approach that links infrastructure performance with sharia values to formulate recommendations for regional development policies in Lampung that are more inclusive, sustainable, and oriented towards long-term welfare.